Makna Hadaka Matsuri di dalam Masyarakat Jepang Dewasa ini: Studi Kasus dari Saidaiji Eyou di Okayama, Jepang - Nadya, Frieska Sekar (Bina Nusantara University, 2009)
Japan has traditional cultures which are still persisted and maintained until now. One of them is matsuri. Matsuri is a religious event which was held by at least one unit of the family to serve kamisama (Gods). One of these events is hadaka matsuri. Hadaka matsuri which still persists till now is Saidaiji Eyou in Okayama. In the Saidaiji Eyou, the participants tried to get the shingi so they can obtain luck during the coming year. Yanagita Kunio defined matsuri into two, matsuri itself and sairei. Sairei is a religious event which was enourmously held and watched by many audiences (Yoneyama Toshinao, 1986:171). Saidaiji Eyou can be categorized as one of sairei form because it is enourmously held, if it is compared with the previous implementation. But, it does not mean that the change of the matsuri into sairei is a decaying point for any religions or cultures in Japan. Oppositely, this change is used as a moment by the Japanese to persist the matsuri itself.Â Â